¡Revolución Sin Fronteras! Mexican Immigrants, Mexican-Americans, and Magonistas in Los Angeles, 1900-1930 - Aguilar, Salvador (The Toro Historical Review, 2019)
From the 1900s to the 1930s, the Anglo power structure in Los Angles silenced all groups who challenged their rule. Ricardo Flores Magón, who was the intellectual writer for the Mexican Revolution in the early 20th century, resisted the Mexican dictator Porfirio Diaz and the Anglo rule in Los Angles. This paper argues that the Anglo power system targeted Magonistas, followers of Ricardo Flores Magón, Mexican immigrant workers, and Mexican Americans during the Mexican Revolution to prevent an uprising in Los Angeles and to maintain close economic ties with Porfirio Diaz and Mexican elites in general. To prove my thesis, I utilized the Archivo Digital de Ricardo Flores Magón. This online archive contains Ricardo Flores Magón’s newspapers Regeneración and Revolucion. I also utilized the Los Angeles Times Historic. This online archive contains all newspaper articles published by the Los Angeles Times. I used the two newspapers to compare the Magonista and Anglo perspectives. The third online archive I used was the Strachwitz Frontera Collection which contains music written by Mexican and Mexican Americans. The final online primary source collection that I referenced was the Anarchist Library. This online collection contains various documents written by anarchists; including the works written by Ricardo Flores Magón. Using the four primary source collections will support my thesis.